THE DISCREPANCY BETWEEN PERCEIVED AND OBSERVED TEACHING CREATIVITY OF ENGLISH TEACHERS IN SMA N 2 BANGLI - Yudha, Yohanes Satria Indra; Artini, Luh Putu; Padmadewi, Ni Nyoman (Language and Education Journal Undiksha, 2020)
This study aimed to identify the discrepancy between the perception and the implementation of the English teachers’ creativity in teaching. This study used mixed method with embedded design in which the qualitative data were more dominant than the quantitative data. This study was conducted in SMA N 2 Bangli. Two English teachers of SMA N Bangli were selected as research subjects. The research instruments used to collect the data namely self-rated questionnaire, classroom observation sheet and in-depth interview. The result of this research shows that there is a discrepancy between the teachers’ perception and their implementation towards creativity in teaching in the learning process. The discrepancy occurred because the degree of motivation, limitation facility, subjective judgement and their creativity in teaching was not optimal yet. Moreover, the teachers also preferred to teach the students directly, deductively and conventionally and rarely to create various creative activities in the learning process.